PENGHAMBATAN ENZIM TIROSINASE dan AKTIVITAS ANTIOKSIDAN EKSTRAK BUNGA TELANG (Clitoria ternatea) MENGGUNAKAN METODE DPPH - Bayu Febram Prasetyo; Amrozi; Nur Anisa BS (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Clitoria ternatea or known as the butterfly pea is widely used in the health sector due to its efficacy as antidiabetic, anti-inflammatory, antimicrobial, anticancer, analgesic, antipyretic, and antioxidants. The purpose of this research is to examine the antioxidants and tyrosinase inhibitor activities of butterfly pea ethanol extract as well as to identify the phytochemical content. Antioxidants activities are determined by the DPPH method. The results of this study indicates that butterfly pea extract has very weak antioxidant activities with an IC50 value more than 200 ppm. The results of the tyrosinase inhibitor activities showed that the butterfly pea extract did not inhibit the tyrosinase enzyme. Based on the screening phytochemical tests, the chemical components contained in butterfly pea extract are flavonoids, tannins, saponins, and steroids. Bunga telang flower extract has very weak antioxidant activity and tyrosinase inhibitor testing showed antioxidant flower extract by DPPH method. Tyrosinase inhibitor assay results showed white Bungatelang extract has no activity to inhibit tyrosinase enzyme.